2015
DOI: 10.1021/acs.jpcc.5b02370
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric Spectroscopy Study of Water Behavior in Calcined Upsalite: A Mesoporous Magnesium Carbonate without Organic Surface Groups

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Apart from the difference in the MgO content, the MMC in this study had no differences in the composition when compared with the materials presented in our previous studies (<20 wt%, compared to $50 wt% previously). 22,23,47,50,51,62 Aggregate formation mechanism…”
Section: The Pore System Of and The Surface Of MMCmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from the difference in the MgO content, the MMC in this study had no differences in the composition when compared with the materials presented in our previous studies (<20 wt%, compared to $50 wt% previously). 22,23,47,50,51,62 Aggregate formation mechanism…”
Section: The Pore System Of and The Surface Of MMCmentioning
confidence: 99%
“…One may expect that such surfactant-free synthesis routes, where calcination at high temperatures is not needed, may be important for the up-scalable production of mesoporous materials. The industrial feasibility of the MMC is further emphasised by the material's moisture sorption properties, [47][48][49][50] biocompatibility 51 and drug stabilising properties. 22,23 Most recently we also showed that MMC has the ability to prevent blood clotting, 52 which opens up its potential for application where blood clotting needs to be suppressed.…”
Section: Introductionmentioning
confidence: 99%
“…In 2013, we presented the template-free synthesis of a mesoporous magnesium carbonate (MMC) material, commercialized as Upsalite, that is synthesized in a low-temperature process and has a well-defined pore size distribution . In addition to its ability to absorb a large amount of moisture, ,, this material has recently been found to be able to stabilize poorly soluble drugs incorporated into the mesopore structure of the material, thus enhancing their dissolution rate. , The material, which consists of amorphous magnesium carbonate and a small portion of crystalline magnesium oxide, has further been indicated to be safe to use on skin as it, even at very high concentrations, was shown to be nontoxic for human dermal fibroblast cells and to not induce cutaneous reactions in in vivo skin irritation tests. In addition, no evidence of systemic toxicity was found when saline extracts of the material were injected in mice …”
Section: Introductionmentioning
confidence: 99%
“…The chemical stability of CAP-MMC was evaluated during a three-month storage period, using Captex as a reference. Amorphous material (here relating to the MMC) is more prone to undergo solid-state changes in humid conditions [30], and to minimize cofounding effects due to adsorption of water on the MMC the study was performed under dry conditions [31]. For each sampling point, 300 mg of formulation was prepared as described in Section 2.2.1 in semi-open vials and placed in a stability chamber containing phosphorus pentoxide and silica gel (<5% RH/25 • C).…”
Section: Stability Evaluation Of Captex-loaded MMCmentioning
confidence: 99%